TEACHERS’ ROLES IN ENGLISH CLASSROOM MANAGEMENT AT THE EIGHTH GRADE OF SMP NEGERI 4 TANJUNGPINANG - Firstanada Jenni Yulieta Siagian; Bahagia Saragih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This research dealt with teachers' roles used by English teachers in English classroom management. This study aimed to investigate the types of teachers' roles were used by the English teachers and to analyze the reasons why teachers applied their roles in the way they did in English Classroom management at the eighth grade of SMP Negeri 4 Tanjungpinang. A descriptive qualitative design was used in this study. The data in this study were collected by using field notes, video recording, and unstructured interviews with teachers. The data were analyzed by data reduction, data display, and drawing conclusions. The findings of this study showed that the two teachers who taught in the eighth grade of SMP Negeri 4 Tanjungpinang applied these eight roles to manage the classroom during teaching and learning. But there are differences between the roles performed by them when the teaching and learning process takes place in the classroom. The first teacher (W) applied the seven teacher’ roles as controller, organizer, assessor, participant, resource person, tutor, and observer. The second teacher (R) applied seven teacher’ roles as controller, organizer, assessor, and prompter, resource person, tutor, and observer. The reason why the both of English teachers in the eighth grade at SMP Negeri 4 Tanjungpinang applied their roles as they did. Because of 1) teachers’ formative, 2) teachers’ training experience, and 3) teachers’ personal attributes.Keywords : Teachers’ Roles, English Teacher, Classroom Management